Chemical Composition Stabilized Rice Bran Milling Fractions And Characterization Of Their Ferulic Acid Rich Extracts - Raja Sulaiman, Raja Rohaya (2010)
The research was carried out to study the characteristics of local stabilized rice bran. Four rice bran-milling fractions, after stabilized by microwave heating, were analyzed for their chemical composition. Its potential as a source of phenolic antioxidants was investigated by assessing the Total Phenolic Compounds (TPC) by spectrophotometry and the effect of stabilization. The fraction with the highest yield of TPC was subjected to High Performance Liquid Chromatography (HPLC) analysis for phenolic compounds profiling. The yield and selectivity of different extraction solvents for phenolic compounds analysis were investigated. Phenolic acid content of the crude extract of the 1st Rice Bran Milling Fraction which fractionated by Sephadex LH-20 column chromatography was determined by HPLC. The antioxidant capacity of isolated rice bran extracts were assayed by Ferric Thiocyanate (FTC) and Thiobarbituric Acid Reactive Substances (TBARS). Results showed that all milling fractions especially the 1st fraction were rich in fat, protein, carbohydrates and total dietary fibre (TDF). The TPC found in rice bran in decreasing order was: Fraction 1 > Fraction 3 > Fraction 2 > Fraction 4. The TPC of all fractions were detected at 257-488 mg ferulic acid equivalent/kg. The stabilization gave no losses of phenolic compounds in all bran fractions studied except for Fraction 3. The efficiency of various solvent to extract phenolic acids from rice bran in decreasing order was: 1 % acidified water > ethanol > acetone ≈ methanol > ethyl acetate. The 1st rice bran milling fraction contained highest of ferulic acid, followed by p-coumaric, caffeic acid and sinapic acid. Rice bran was found to be potentially a source of phenolic compounds particularly the 1st milling fraction. The amount of TPC in fractionated extracts (Fraction A – D) was about 6-folds higher than that in stabilized rice bran. Fraction C and D contained higher ferulic acid at 831.51 and 841.54 ppm; respectively, may ideally serve as the ferulic acid-rich extracts. FTC and TBARS methods showed Fraction A - D possessed significantly higher inhibition activities than that of α-tocopherol. Thus, the fractionation employed was efficient in obtaining the ferulic acid rich-extracts with comparable antioxidative activities. Apart from increasing the utilizations of local raw materials, the first rice bran fraction was found to be an excellent source of energy, fat, mineral and could be a very good source of dietary fiber and other nutrients especially many health-promoting components such as ferulic acid. Therefore, the rice bran fraction can be a potential natural source of antioxidants or as a value–added product to variety of functional foods.